2021
DOI: 10.1002/ange.202016764
|View full text |Cite
|
Sign up to set email alerts
|

GlycoBODIPYs: Sugars Serving as a Natural Stock for Water‐soluble Fluorescent Probes of Complex Chiral Morphology

Abstract: A range of unprocessed, reducing sugar substrates (mono-, di-, and trisaccharides) is shown to take part in a straightforward four-step synthetic route to water-soluble, uncharged BODIPY derivatives with unimpaired chiral integrity and high fluorescence efficiency. A wide compatibility with several postfunctionalizations is demonstrated, thus suggesting a universal utility of the multifunctional glycoconjugates, which we call GlycoBODIPYs. Knoevenagel condensations are able to promote a red-shift in the spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The constructed glycoconjugates, regardless of the incorporated sugar moiety, exhibit generally solvent-independent fluorescence effectiveness, which preserves all of the spectroscopic benefits of the BODIPY motif. Confocal imaging research revealed a variety of glyco-BODIPYs’ applications for cellular studies and illustrated their powerful chiral activity for particular cellular applications …”
Section: Applications Of Bodipymentioning
confidence: 99%
See 1 more Smart Citation
“…The constructed glycoconjugates, regardless of the incorporated sugar moiety, exhibit generally solvent-independent fluorescence effectiveness, which preserves all of the spectroscopic benefits of the BODIPY motif. Confocal imaging research revealed a variety of glyco-BODIPYs’ applications for cellular studies and illustrated their powerful chiral activity for particular cellular applications …”
Section: Applications Of Bodipymentioning
confidence: 99%
“…Confocal imaging research revealed a variety of glyco-BODIPYs' applications for cellular studies and illustrated their powerful chiral activity for particular cellular applications. 36 2.6. Metal Ion Detection.…”
Section: Acs Appliedmentioning
confidence: 99%
“…The two carborane polymers (35,36) exhibit great biocompatibility was immediately and precisely detected, according to the results of cell imaging. It offers a fresh concept for BNCT research and design.…”
Section: Anti-cancermentioning
confidence: 99%
“…Confocal imaging research revealed a variety of GlycoBODIPYs' applications for cellular studies and illustrated their powerful chiral activity for particular cellular applications. 36 Fig. 25 Glyco-BODIPY complexes.…”
Section: Bioimagingmentioning
confidence: 99%
“…24 However, dipyrromethene is a versatile N,N-ligand of boron, and has been used for the synthesis of various fluorescent BODIPY molecules. [25][26][27] The non-dipyrromethene scaffold has also been used for the synthesis of BODIPY type fluorescent molecules, and BODIPY analogues, by N,N-/N,Ochelation. [28][29][30] Previously, aminotropone derivatives have also been explored for preparing novel fluorescent molecules, BODIPY analogs, by complexing with BF 2 through N,N-/N,O chelation (Fig.…”
Section: Introductionmentioning
confidence: 99%